2019
DOI: 10.1101/572479
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Symbiont community diversity is more constrained in holobionts that tolerate diverse stressors

Abstract: AbstractCoral reefs are experiencing global declines as climate change and other stressors cause environmental conditions to exceed the physiological tolerances of host organisms and their microbial symbionts (collectively termed the holobiont). To assess the role of symbiont community composition in holobiont stress tolerance, diversity metrics and abundances of obligate dinoflagellate endosymbionts (Family: Symbiodiniaceae) were quantified from eight Acropora mil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Another consideration is the contribution of the algal symbiont toward holobiont health. In this study, colonies primarily hosted Cladocopium symbionts almost exclusively, but also contained lower abundances of Brevolium, Durusdinium, and/or Gerakladinium symbionts (<0.1% of the total community; Howe- Kerr et al, 2019).…”
Section: Best Performing Genets Tolerate Multiple Stressorsmentioning
confidence: 64%
See 1 more Smart Citation
“…Another consideration is the contribution of the algal symbiont toward holobiont health. In this study, colonies primarily hosted Cladocopium symbionts almost exclusively, but also contained lower abundances of Brevolium, Durusdinium, and/or Gerakladinium symbionts (<0.1% of the total community; Howe- Kerr et al, 2019).…”
Section: Best Performing Genets Tolerate Multiple Stressorsmentioning
confidence: 64%
“…The final total genets for each sampling location are as follows: Davies ( n = 10), Rib ( n = 10), Pandora ( n = 14), and Esk ( n = 6). Algal symbiont types were investigated by ITS‐2 sequencing for eight of the coral colonies (Howe‐Kerr et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The physiological performance of corals can be significantly affected by their Symbiodiniaceae community composition (Oliver and Palumbi, 2011;Palumbi et al, 2014;Howe-Kerr et al, 2019;Eckert et al, 2020). Here, we found that Symbiodiniaceae community composition was associated with the interaction of the amount of weight gained and transplant location at the Gardens site, and may also have contributed to heat tolerance.…”
Section: Discussionmentioning
confidence: 64%
“…However, it is also possible that a symbiont that translocates less material might end up becoming specialized for a particular host before a "better" symbiont partner could become entrained in the host's biology. Recent observations that more diverse symbiont communities are found in holobionts less resistant to environmental stressors (Howe-Kerr et al, 2020) might be explained by a lack of tight specialization between host and symbiont.…”
Section: General Observationsmentioning
confidence: 99%